Implementasi Penggunaan Quizizz Pada Mata Pelajaran Sejarah Untuk Meningkatkan Motivasi Belajar Siswa Kelas X-10 SMA Negeri 1 Palangka Raya - Rejeki, Sisilia Sri; Susanto, Yudi (Universitas Syiah Kuala, 2025)
The utilization of media in the learning process has great potential to stimulate students' interest and motivation, prevent boredom, and improve the quality of the learning process and results. One of the innovations used in this study is the use of learning media in the form of Quizizz, an online platform that allows the creation of quizzes that are interactive, fun, and interesting for students. This study aims to explain the implementation and results of the implementation of online-based learning media in the form of Quizizz to increase students learning motivation in History subjects.The research method used is kuantitatif with descriptive research type. The research subjects used by the researchers were students of class X-10 at SMA Negeri 1 Palangka Raya, a total of 40 students. The research design is The One Group Pretest-Posttest. Data collection techniques using questionnaires and documentation. The collected data were analyzed using descriptive percentage techniques. The results showed that the use of learning media such as Quizizz can be effectively implemented and can create a fun and interesting learning atmosphere. The application of Quizizz is proven to be able to increase students' motivation to learn as seen from the increase of 15.8% in the difference in the average percentage value between Pretest and Posttest from meeting I to meeting II. This shows that Quizizz as a learning media not only makes the learning process more interesting, but also significantly increases students learning motivation